Multi-objective job shop scheduling problem with sequence dependent setup times using a novel metaheuristic. (1st January 2014) - Khalili, Majid; Naderi, Bahman
The job shop problem is the most complicated and typical problem of all kinds of production scheduling problems, the allocation of resources over time to perform a collection of tasks. This paper studies multi-objective job shop scheduling problems where the setup times is sequence dependent to minimise two objective functions simultaneously. Since the problem is NP-hard and difficult to find an optimal solution in a reasonable computational time an efficient multi-objective electromagnetism algorithm (MOEA) is presented as the solution procedure. An electromagnetism algorithm is known as a flexible and effective population-based algorithm utilising an attraction/repulsion mechanism to move the particles towards optimality. The algorithm is carefully evaluated for its performance against two available algorithms by means of multi-objective performance measures and statistical tools. All the results demonstrate that our MOEA is very effective for the problem.